NPWP vs NIK: Integrating the Single Identity Number in Taxation - Rizka Amila; Resi Ariyasa Qadri (Research Synergy Foundation, 2023)
The policy of integrating National ID Numbers and Tax ID Numbers as the government's initial effort to implement a Single Identity Number has various challenges in its implementation. Perceptions between policymakers that differ from public perceptions are one of the main problems that must be considered. This research was conducted to find out the perceptions and expectations of Taxpayers and Frontline Officers at the tax office regarding the implementation of the National ID Number and Tax ID Number integration policy. Data collection was carried out by literature study and interviews with 2 Taxpayers and 2 Frontline Officers. The analytical method used is qualitative descriptive analysis with an inductive approach. The research results show that there is a gap in perception between Taxpayers and the Directorate General of Taxes (DGT) due to the lack of publications where Taxpayers hope that updating data in the context of integrating National ID Numbers with Tax ID Numbers can be done automatically through the system. Frontline Officers also hope there will be no more obstacles in the updating process so that it does not disrupt other services. With this research, the writer hopes that it can become input for the DGT in making policies by considering the constraints and obstacles that may occur in its implementation so that policies can run optimally.